A typological study of vowel interactions in Basque - Varun deCastro-Arrazola (Universitat Autònoma de Barcelona, 2015)
The aim of this paper is to check the factorial typology for a set of phonological constraints on vowel interactions in Basque against corpus data (Hualde and Gaminde 1998, Euskararen Herri Hizkeren Atlasa, ‘The Basque Dialectological Atlas’) with the help of OT-Help 2.0 (Staubs et al. 2010), a specialized software that calculates factorial typologies. The formal analysis developed to account for different patterns of vowel interactions in Basque, including those patterns displaying phonological opacity, implements Element Theory (Backley 2011) in Turbidity Theory (Goldrick 2001, Van Oostendorp 2008). The proposed analysis has the virtue of predicting all attested patterns of a specific type of vowel interactions in Basque and excluding the unattested patterns.